Political Participation of Minors in India - Poddar, Rongeet (University of Jember, 2023)
The participation of children in a political demonstration has proven to be an enduring issue in India owing to the public agitations against the Citizenship Amendment Act and the farm laws, with the latter being withdrawn recently. Under the hegemonic liberal paradigm, the underlying risk is that civil and political rights may be envisaged as the exclusive domain of adults. Children are merely viewed as apprentice citizens who do not have the capacity to exercise rational choice. The operative presumption is located in a binary wherein children are pliant beneficiaries, and the state is a benign caretaker in charge of determining their best interests. It thereby negates children’s autonomy and reduces them to disenfranchised spectators in an adult-centric social fabric. Moreover, the protectionist approach enables the state to evade its obligation of preserving democratic spaces wherein minors can protest safely and make their voices heard. State functionaries and judicial authorities in India have also been complicit in adopting an infantilising stance. In this paper, the author makes a case for recognising the agency of children such that they can exercise their ‘autonomy’ right to political participation. This paper incorporates diverse perspectives in existing child rights literature, including those emanating from the Global South, to argue in favour of an epistemic reorientation in child rights law discourse. Moreover, the author relies upon key interpretations of UNCRC provisions made by the Committee on the Rights of the Child and argues for facilitating a participative environment where children can exercise their civil and political rights. The ‘best interests’ test should not be wielded as a sword from an adult standpoint to curtail children’s rights in the political domain.Keywords: Children's Rights, Citizenship Act, Political Participation.